GroEL/ES inhibitors as potential antibiotics. Issue 13 (1st July 2016) - Abdeen, Sanofar; Salim, Nilshad; Mammadova, Najiba; Summers, Corey M.; Frankson, Rochelle; Ambrose, Andrew J.; Anderson, Gregory G.; Schultz, Peter G.; Horwich, Arthur L.; Chapman, Eli; Johnson, Steven M.
Graphical abstract: Abstract: We recently reported results from a high-throughput screening effort that identified 235 inhibitors of the Escherichia coli GroEL/ES chaperonin system [ Bioorg. Med. Chem. Lett. 2014, 24, 786]. As the GroEL/ES chaperonin system is essential for growth under all conditions, we reasoned that targeting GroEL/ES with small molecule inhibitors could be a viable antibacterial strategy. Extending from our initial screen, we report here the antibacterial activities of 22 GroEL/ES inhibitors against a panel of Gram-positive and Gram-negative bacteria, including E. coli, Bacillus subtilis, Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter cloacae . GroEL/ES inhibitors were more effective at blocking the proliferation of Gram-positive bacteria, in particular S. aureus, where lead compounds exhibited antibiotic effects from the low-μM to mid-nM range. While several compounds inhibited the human HSP60/10 refolding cycle, some were able to selectively target the bacterial GroEL/ES system. Despite inhibiting HSP60/10, many compounds exhibited low to no cytotoxicity against human liver and kidney cell lines. Two lead candidates emerged from the panel, compounds8 and18, that exhibit >50-fold selectivity for inhibiting S. aureus growth compared to liver or kidney cell cytotoxicity. Compounds8 and18 inhibited drug-sensitive and methicillin-resistant S. aureus strains with potencies comparable to vancomycin, daptomycin, and streptomycin, and are promising candidates to explore for validating the GroEL/ES chaperonin system as a viable antibiotic target.